Molecular Dynamics Simulation Study: Mechanism Of Cationic And Anionic Dyes Adsorption On Montmorillonite - Febriati Dian Mubarokah; Mia Ledyastuti; Muhammad Ali Zulfikar (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Discharging dye-containing wastewater can severely degrade water quality. Adsorption is widely studied because it is selective, effective, and relatively low cost. This work examines adsorption of a cationic dye, crystal violet (CV), and an anionic dye, congo red (CR), on montmorillonite clay (MMT) using molecular dynamics simulations in GROMACS. Molecular topologies were built with a combined ClayFF and CHARMM36 force field. Simulations used a 6 nm × 6 nm × 6 nm box filled with SPC/E water (spce.gro). After minimization and NVT and NPT equilibration, production runs were carried out for 50 ns (25,000,000 steps) with a 2 fs time step at 300 K and 1 bar. Single-dye and mixed-dye systems were compared to clarify adsorption mechanisms. In the single CV system, the best performance occurred at 20 CV molecules, giving 40% adsorption. Radial distribution analysis indicates that adsorption is dominated by van der Waals interactions between the negatively charged MMT surface and the CV quaternary ammonium site (-N+). In contrast, CR was not adsorbed in the single CR system because electrostatic repulsion prevents approach to the negatively charged clay. In mixed CV–CR systems, adsorption of both dyes increased, revealing synergistic behavior. CV enters the MMT interlayer and forms an organic phase, which then immobilizes CR through hydrophobic interactions, enabling CR adsorption despite its unfavorable electrostatics under realistic wastewater conditions.